Colorado climate encyclopedia entry - Goble, Peter, author; Doesken, Nolan, author (Colorado State University. Libraries, 2017)
A report, with supporting graphics, detailing the climate of Colorado.--taken from website.
Keywords: Colorado -- Climate -- Observations; Climatic changes -- Colorado; Meteorology -- Colorado -- Observations